(untitled) (Mugda Medical College Journal, 2023)
Background: Prostatic lesions like nodular hyperplasia, inflammation and carcinoma are common causes of morbidity and mortality in males. The incidence of these lesions increases with advancing age. Prostatic diseases show varying incidence in different geographical locations worldwide. Objectives: To evaluate the histopathological spectrum of various prostatic lesions in biopsy specimen. Methods: This was a retrospective study comprising 220 cases, carried out at the Department of Pathology, Enam Medical College and Hospital from January 2014 to December 2020. The histopathological slides were analyzed according to type of specimen, age of the patient, and histopathological pattern. Adenocarcinomas were graded according to Gleason score. Results: Of the total 220 specimens, 202 (91.8%) were of nodular hyperplasia, 14 (6.4%) were carcinoma and 4 (1.8%) cases were high grade prostatic intraepithelial neoplasia (HGPIN). All the cases of prostatic malignancies were adenocarcinoma and majority were belonged to Gleason’s score 7. Maximum numbers of cases of nodular hyperplasia were seen in the 61-70 years age group and carcinomas were peak in the 71-80 years age group. Conclusion: Non-neoplastic lesions of the prostate are more common than neoplastic ones. Histopathological diagnosis and grading plays a definitive role in the management of prostatic carcinoma. Mugda Med Coll J. 2023; 6(1): 5-10